2011
DOI: 10.1097/scs.0b013e3182326dfb
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Protruding Ear

Abstract: Protrusion differs significantly between sexes. This indicates that different criteria should be used to judge protrusion in boys and girls. None of our prominent ears exceeded only the demarcation in the lower protrusion, suggesting that upper protrusion plays a larger role in the perception of prominence than lower protrusion and should therefore be the main objective of corrective otoplasty. Furthermore, the variation of asymmetry of protrusion in the normal population indicates that an often used success c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
0
22
1
1
Order By: Relevance
“…Moreover, many authors have reported significant intergender differences regarding this feature (Driessen et al, 2011). Our observed insignificant differences concerning this trait do not confirm this hypothesis.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Moreover, many authors have reported significant intergender differences regarding this feature (Driessen et al, 2011). Our observed insignificant differences concerning this trait do not confirm this hypothesis.…”
Section: Discussioncontrasting
confidence: 55%
“…In Bulgaria Todorov, Gavrilovič (1990) examined the Bulgarian population in connection with the presence of Darwin's tubercle (tuberculum auriculae Darwini) without specifying the study area. Although protruding ears are among the most common congenital deformities in craniofacial area, clear consensus in literature in terms of their determination is still absent (Driessen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lower protrusion should not exceed more than 20.0 mm in males and 15.5 mm in females. Upper protrusion plays a more important role in the perception of prominence as compared with lower protrusion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the current study, for all facial forms, ear visibility is approximately 1.5 cm in upper protrusion. According to Driessen et al, upper protrusion should not exceed more than 21.5 mm in males and 17.5 mm in females [13]. Lower protrusion should not exceed more than 20.0 mm in males and 15.5 mm in females.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of protrusion in frontal 3 facial photographs was performed by Driessen et al (Driessen, Borgstein, & Vuyk, 2011) in a 4 retrospective investigation of 44 patients with protruding ears and 102 prospectively collected 5 normal controls. The author used the subjects' irises for calibrating measurements and 6 outlined a methodology for measuring protruding ears in frontal facial photographs.…”
mentioning
confidence: 99%